Bahasa Gaul Santri sebagai Penanda Budaya Baru: Studi Antropolinguistik tentang Tren, Identitas, dan Negosiasi Makna: Santri Slang as a Marker of a New Culture: An Anthropological Linguistic Study of Trends, Identity, and the Negotiation of Meaning - Trina Ningsih; Ali Manshur; Zohaib Hassan Sain (ELOQUENCE : Journal of Foreign Language, 2026)
Background: Santri slang developed in Islamic boarding schools as a response to digital culture and modernity that influenced santri communication practices. Purpose: This study aims to analyze santri slang as a marker of new culture in terms of its linguistic form and social function. Method: The research used a qualitative approach with a linguistic ethnography design. Data were obtained through observation and interviews with junior students, senior students, and boarding school administrators. Data analysis was conducted interactively through reduction, presentation, and conclusion drawing with data triangulation. Results and Discussion: The results of the study show that santri slang is formed through the adoption of pop culture, lexical creation, and code mixing. This practice serves to build collective identity and strengthen social solidarity, while filling a gap in previous studies that viewed santri slang in a partial manner. Conclusions and Implications: The slang used by santri reflects the negotiation between pesantren tradition and modernity. These findings enrich sociolinguistic and anthropological linguistic studies and open up further research opportunities on language and identity in religious communities